Analisis Penambahan Ruang Rawat Inap VIP di RSUD Besemah Kota Pagar Alam - Rora Fitri Dewanti; Lilis Suryani; Heriziana (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
The addition of a VIP inpatient room requires a hospital plan that is truly based on the environmental conditions encountered in order to harmonize the wishes of the community. This is important to avoid the addition of inpatient rooms being wasted due to the wishes and needs of the community. The study was conducted to look at internal factors and thus obtain a picture that directs and provides the basis for the addition of VIP inpatient rooms. This research is a descriptive case study with quantitative and qualitative approaches. The research subjects were 6 people from the management of the Pagar Alam City Hospital. The data used were taken from document review, in-depth interviews and observations. Data analysis was carried out using SWOT analysis. The results of the SWOT analysis of the addition of VIP inpatient rooms are in the matrix it can be seen that the position of Besemah Hospital is at 1.07 on Strength and 0.97 on Opportunity. So is quite feasible to add VIP inpatient rooms and can provide benefits if the Strength factor is optimized and can take full advantage of the Opportunity factor